Advanced Solid-State Battery Technologies for Sustainable Energy Storage - Jyoti AmitKumar Dhamecha (International Journal of Solid State Innovations & Research, 2026)
The increasing global demand for sustainable and high-performance energy storage systems has accelerated research in advanced battery technologies. Conventional lithium-ion batteries, while widely used in portable electronics, electric vehicles, and grid storage systems, face limitations such as safety risks, limited energy density, slow charging rates, and degradation over repeated cycles. To overcome these challenges, advanced solid-state battery technologies have emerged as a promising solution for next-generation energy storage applications. This paper presents a comprehensive study of advanced solid-state battery technologies focusing on their structure, working principles, materials, and performance characteristics. Solid- state batteries replace the conventional liquid electrolyte with solid electrolytes, which significantly enhances safety by eliminating leakage, flammability, and thermal runaway risks. In comparison to conventional lithium-ion systems, these batteries also provide superior thermal stability, longer cycle life, and higher energy density. The study discusses various solid electrolyte materials such as ceramic-based, polymer-based, and hybrid electrolytes, highlighting their advantages and limitations. Additionally, it examines electrode–electrolyte interface engineering, which is essential for lowering interfacial resistance and increasing ion transport efficiency. Furthermore, the paper analyzes manufacturing challenges, including scalability, material cost, and stability issues, which currently limit large-scale commercialization. Emerging solutions such as nanostructured electrolytes, thin-film solid-state batteries, and advanced fabrication techniques are also discussed. The paper concludes that solid-state battery technology is a key enabler for sustainable energy storage systems, offering significant improvements in safety, efficiency, and performance for future applications such as electric vehicles, renewable energy integration, and portable electronics.
Keywords: Energy storage; Solid-state batteries; battery technology; lithium-ion replacement; solid electrolytes; sustainable energy